INTERPERSONAL ANALYSIS OF DONALD TRUMP’S EMOTIONAL LANGUAGE - Erick Firmansyah (Kajian Linguistik dan Sastra, 2019)
The victory of Donald Trump in 2016 US Presidential Election marks the rise of Post-truth era at which objective truth is less important than the emotional truth. This paper analyses interpersonal metafunction of his emotional languages in his campaign speeches. The data are obtained from his speech transcripts. The emotion involves fear, warmth, and humour. They are detected using theory of prototype scenario developed by Wierzbicka (1992) and is analyzed using the perspective of Halliday and Matthiessen’s Systemic Functional Linguistics (SFL) (2004). The analysis focuses on Mood, Modality, and Appraisal Technique. The finding shows the use of all Mood system to convince his audiences, the dominant use of modal item will as median value of obligation, and various use of repetition technique.